Digital models 3D in the teaching-learning process of the medical sciences - José Manuel Izquierdo Pardo; María Elena Pardo Gómez; José Manuel Izquierdo Lao (Centro Provincial de Información de Ciencias Médicas, 2020)
Medical Sciences universities should adapt to the changes imposed by the technological advances at the present time. Digital models 3D facilitate the delivering of contents related  to anatomical, morphological objects and medical phenomena that occasionally, can be complicated and/or abstract for the students. With this work it is intended to analyze the advantages associated with the use of such models in the teaching - learning process of the Medical Sciences careers, since an insufficient technological culture exists in professors of these careers taking into account the wide possibilities that digital models 3D can offer to support the specific contents of subjects, which limits the development of the teaching-learning process. Such models can be incorporate as important didactic means of last generation, which tend to achieve better motivation and understanding levels of the contents on the students.